Determination Of Optical Constant of a Clear Glass Material for Accurate Daylighting and Solar Heat Gain Assessment Using Spectrophotometer Measurements - Khoukhi, Maatouk; Khatib, Omar Al (International Journal of Membrane Science and Technology, 2023)
Many qualities make glass attractive, as it is transparent, chemically inert, environmentally friendly, sustainable, strong, easily available and relatively cheap. Recently, many researchers have been interested in designing the buildings to get the benefit from daylight inside, which saves a lot of building consumption for artificial lighting, which gives visual and thermal comfort and also contributes to reducing costs. The complex refractive index of glass is a very crucial concept because it determines not only how much light is reflected and transmitted, but also its angle of refraction in glass. The optical constants of glass material are very useful for determining its radiative properties, as well as for selecting the appropriate thin-film coatings on a glass substrate. The objective of this study is to calculate the real part (n) and the imaginary part (k) of the complex refractive index of a clear glass material using a simple method based on the reflectivity and transmissivity measurements. In this study, the parts n and k are derived from the equations of the reflectivity at near zero incidence and transmissivity at normal incidence by using Shimadzu IR-70 Spectrophotometer and Cary 5E Spectrophotometer apparatuses. The real and the imaginary parts of the complex refractive index of the glass sample obtained in the present study are in very good agreement with Rubin’s data. Although, a direct comparison between different samples is not possible, due to the difference in manufacturing process and material composition.